PERSISTENT CUTANEOUS BOVINE PAPILOMATOSIS IN AN INDIGENOUS HEIFER AND ITS SUCCESSFUL MANAGEMENT - Jana, Debasis; Ghosh, Mousumi (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Bovine cutaneous papillomatosis or warts are regarded as either hyperplasia or benign neoplasms caused by Bovine Papilloma Virus (Boiron et al., 1965). The lesions were often found in clusters and were more common on shoulder, head, neck and dewlap in cattle (Vahida and Jaya Kumar 1999). However, extensive generalized and or whole body papillomatosis are also not uncommon. The present communication recorded papilloma on the dewlap below the jugular furrow of a non descript heifer and its successful management.
Keywords: PERSISTENT; INDIGENOUS HEIFER; MANAGEMENT